Reviewing and Updating of MBBS Curriculum 2002: Intern Doctors' Views - Talukder, Md Humayun Kabir; Hossain, Md Zakir; Hanif, Md Abdul; Akther, Nasrin; Perveen, Ismat Ara (Bangladesh Journal of Anatomy, 2011)
This cross-sectional study was conducted to explore the views of intern doctors regarding reviewing & updating of MBBS curriculum 2002. This study was conducted upon 257 intern doctors of different government and non government medical colleges in Bangladesh. Data were collected using self administered structured questionnaire using purposive sampling. Study revealed that the contents of the course, the teaching methods and the assessments system for the undergraduate medical students needs few improvement as majority of the intern doctors viewed those areas of the curriculum are all right and few of them opined for change. Study revealed that the formative & summate assessments, carry on system, block posting and duration of internship should be redesigned & rethink to make the curriculum more user friendly and effective as intern doctors have different opinions regarding these issues. Study also recommended that more extensive study is needed to get unanimous opinion from the intern doctor's of the medical colleges to review and update the MBBS curriculum 2002. Key words: Review; Update; MBBS Curriculum DOI: http://dx.doi.org/ 10.3329/bja.v9i1.8146 Bangladesh Journal of Anatomy January 2011, Vol. 9 No. 1 pp 35-40